Noble metal-coated MoS2 nanofilms with vertically-aligned 2D layers for visible light-driven photocatalytic degradation of emerging water contaminants. Issue 1 (December 2017) - Islam, Md; Church, Jared; Han, Changseok; Chung, Hee-Suk; Ji, Eunji; Kim, Jong; Choudhary, Nitin; Lee, Gwan-Hyoung; Lee, Woo; Jung, Yeonwoong
Abstract Two-dimensional molybdenum disulfide (2D MoS2 ) presents extraordinary optical, electrical, and chemical properties which are highly tunable by engineering the orientation of constituent 2D layers. 2D MoS2 films with vertically-aligned layers exhibit numerous 2D edge sites which are predicted to offer superior chemical reactivity owing to their enriched dangling bonds. This enhanced chemical reactivity coupled with their tunable band gap energy can render the vertical 2D MoS2 unique opportunities for environmental applications that go beyond the conventional applications of horizontal 2D MoS2 in electronics/opto-electronics. Herein, we report that MoS2 films with vertically-aligned 2D layers exhibit excellent visible light responsive photocatalytic activities for efficiently degrading organic compounds in contaminated water such as harmful algal blooms. We demonstrate the visible light-driven rapid degradation of microcystin-LR, one of the most toxic compounds produced by the algal blooms, and reveal that the degradation efficiency can be significantly improved by incorporating noble metals. This study suggests a high promise of these emerging 2D materials for water treatment, significantly broadening their versatility for a wide range of energy and environmental applications.